Coral conditions and reef fish presence in the coral transplantation area on Kapoposang Island, Pangkep Regency, South Sulawesi. Issue 1 (March 2020) - Ulfah, I; Yusuf, S; Rappe, R A; Bahar, A; Haris, A; Tresnati, J.; Tuwo, A
Abstract: Coral reefs are currently suffering from serious degradation due to human activities. In 2015, the condition of coral reefs in Kapoposang Island has been very poor with the live coral cover only 16%. Therefore, the coral reef ecosystem on this island needs to be rehabilitated. This study aims to assess coral cover based on the age of transplantation and examine abundance of reef fish in relation to age of transplant module at Kapoposang Island which is in the Wallacea region. Coral transplant was carried out from 2014 to 2018. The transplanted corals were corals of the genus Acropora. Transplants were carried out at a depth 3 to 4 m. The determination of the transplant module as the reef fish's observation was based on the age of the transplant module, i.e. 1, 2, 3 and 4 years old. Data collection was carried out using the UVC (Underwater Visual Census) method. Data collection was done by using the UPT (Underwater Photo Transect) method. Photograph data was processed using CPCe (Coral Point Count with Excel extension) software using 30 random points for each frame. The significant relationship between live coral cover and reef fish shows that the coral transplantation was successful. There was linear relation between coral habitat cover and the reef fish. The difference in abundance in each transplant module shows the linier relation between the increase of reef fishes and live coral cover. The live coral cover was higher at the two and three years old of the transplant module. During the study, it was found 13 families and 56 species of reef fish. Planktivorous group was the most dominant of reef fish.